Traditional Chinese medicine nursing of a patient with Qi-deficiency type constipation treated by meridian acupoints massage combined with umbilical moxibustion (经穴推拿联合脐灸治疗1例气虚便秘患者的中医护理体会) - GE Sinan (葛思楠); WANG Xuesong (王雪送); YU Yanlan (余艳兰) (Journal of International Translational Medicine Limited, 2023)
This paper summarized the experience of Traditional Chinese Medicine nursing for a patient with Qi-deficiency type constipation treated by meridian acupoints massage combined with umbilical moxibustion. According to syndrome differentiation of the patient, meridian acupoints massage combined with umbilical moxibustion was carried out to alleviate the symptoms of constipation and Qi-deficiency and improve the recovery of the patient. (本文总结经穴推拿联合脐灸治疗1例气虚便秘患者中医护理体会。根据护理评估以及辨证分型, 在饮食指导、生活起居、情志护理等常规护理基础上给予经穴推拿联合脐灸的中医特色护理, 有助于缓解患者便秘和气虚症状, 有效促进疾病康复。)